THE EFFECT OF DIGITAL WALLET USE ON FINANCIAL BEHAVIOR OF GENERATION Z IN MAKASSAR CITY WITH YOU ONLY LIVE ONCE AS MODERATION - Athaillah Hasyim; Tenri Sayu Puspitaningsih Dipoatmodjo; Annisa Paramaswary Aslam (Jurnal Manajemen, 2026)
Abstract:This study investigates how digital wallet usage influences prudent financial behavior and examines the moderating role of the YOLO lifestyle in this relationship. This quantitative study used survey data from 150 Generation Z respondents in Makassar, Indonesia. Measurements of latent variables such as Prudent Financial Behavior (measured through indicators of planning, budgeting, and spending control) and YOLO Lifestyle (measured as present-oriented and impulsive buying) were validated first. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The results showed that there was a significant negative effect of Digital Wallet Usage on good Financial Behavior (β: -0.464, p-values <0.05). Furthermore, the You Only Live Once lifestyle was proven to strengthen the negative influence of the relationship between the two variables (β, -0.48, p-values <0.05). This shows that the intensity of You Only Live Once in Generation Z amidst the convenience offered by Digital Wallet technology is associated with poor Financial Behavior.Keywords:Financial Behavior, Digital Wallet, Individual Financial Management, You Only Live Once, Generation Z.